Implementation of Gold Bullion Funding as Alternative Instruments to Overcome the Problem of Currency Fluctuation - Supatmojo, Pramesti; Rivenda, Adelia; Aunillah, Muhammad (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2023)
Infrastructure development has an important contribution in improving the national economy and realizing people's welfare. However, there are still problems in the implementation, namely the government's limited ability to fund infrastructure development projects. For this reason, the government has actually attempted to create a mechanism in the form of Public Private Partnership (PPP) by emphasizing risk sharing between the government and the private sector. However, this effort did not run smoothly because there were other risks, one of which was related to project financing which was at risk of currency value fluctuations. This situation shows that there is a need for a solution to optimize project financing in Indonesia through the Gold Bullion Funding (GBF) mechanism. The research method used is normative legal research by utilizing a qualitative method in analyzing data or secondary data through searching regulations and literature related to the object of the problem. Based on the research results, the author initiated the GBF mechanism to answer problems related to the implementation of project finance in PPPs. Regarding its implementation, the GBF mechanism will refer to the OJK regulation regarding the implementation of bullion business activities in order to optimize the government's role in forming the bullion ecosystem in Indonesia. With this mechanism, problems related to currency fluctuations in project finance in Indonesia can be resolved so that development can be realized that is effective, efficient and provides benefits to society.